The Effect of Psychological Suzhi on Problem Behaviors in Chinese Adolescents: The Mediating Role of Subjective Social Status and Self-esteem - Liu, Guangzeng; Zhang, Dajun; Pan, Yangu; Ma, Yuanxiao; Lu, Xingyue (Frontiers in Psychology, 2017)
In this study, we examined subjective social status and self-esteem as potential mediators between the association of psychological suzhi and problem behaviors in a sample of 1271 Chinese adolescents (44.5% male, grades 7–12) . The results showed that subjective social status and self-esteem were found to fully mediate the relation between psychological suzhi and problem behaviors. Moreover, the indirect effect was stronger via self-esteem than via subjective social status. These findings perhaps provide insight into the preliminary effect that subjective social status and self-esteem underlie psychological suzhi’s effect on adolescents’ problem behaviors, and also were important in helping school-teachers and administrators to develop a better understanding of problem behaviors in their schools as a pre-requisite to the development of more effective behavior management practices from the perspective of psychological suzhi. Implications and limitations in the present study have also been discussed.